El Régimen disciplinario y sus reformas - La Actividad probatoria disciplinaria (2022)
Colombian legislation in the disciplinary field does not have a clear understanding of the rules of the game applicable to disciplined subjects, since there has not been a law in force that lasts or contains a concrete and definitive rule. When we talk about the sanctioning power of the Colombian State, we are immersed in a wide field of application, since the law attributes competence to the different territorial entities, as well as to administrative entities in order to establish sanctions when it is considered pertinent as long as there is a lack of duty and consequently an administrative offense occurs, the research method used is the qualitative method because it allowed it to be possible in a conceptual way and through the consultation of the norm, doctrine and jurisprudence to identify that the legal system in the disciplinary field has structurally attacked the Inter-American Convention on Human Rights since the accusatory system is inquisitive and the power that has been given to the attorney general's office sanctions and disables a public servant chosen by popular vote since it undermines representative democracy and participation of a social state of law.